Pathogenic role of lipids in non-alcoholic fatty liver disease - Yu. O. Shulpekova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To discuss main concepts on the damaging role of lipids in non-alcoholic fatty liver diseases (NAFLD) pathogenesis.Original points. According to modern concepts, at NAFLD stress of endoplasmic reticulum plays the central role in damage of liver cells which is accompanied by dysfunction of chaperone proteins. The subsequent biochemical changes cause disorders of cellular respiration, disorder of mitochondrial integrity, increase probability of hepatocyte death. Excessive accumulation of free fatty acids acts as direct impulse for development of endoplasmic reticulum stress, and resulting events inside a cell are named «lipotoxic stress» or «lipoapoptosis». Saturated fatty acids – palmitic and stearinic have maximal damaging potential, that, probably, is related to slower incorporation of esters. In NAFLD pathogenesis other damaging factors, e.g. oxidative stress play important role, therefore the theory of «multiple collateral impulses» is justified today. Unsaturated fatty acids, essential phospholipids, antioxidants, silymarinum, hypolipidemic agents, glitazones can have protective action. Potential of medical application of caspase inhibitors, cathepsine B, JNKkinase and «chemical chaperones» is under investigation.Conclusion. Lipoapoptosis is considered as cardinal marker of NAFLD, and free fatty acids – as activators of the programmed death of hepatocytes. The further studying molecular events at lipotoxic stress will, probably, open new era in the treatment of fatty liver disease.